Copper (I) complexes of a thioether-functionalized short-bite aminobis(phosphonite) - Punji, Benudhar; Mague, Joel T.; Mobin, Shaikh M.; Balakrishna, Maravanji S. (Polyhedron, 2009)
Copper(I) complexes of short-bite aminobis(phosphonite), PhN{P(–OC10H6(μ-S)C10H6O–)}2 (1) have been synthesized. Reactions of 1 with an excess of CuX (X = Cl, Br, and I) afforded the ligand-bridged binuclear complexes, [PhN(PR-κP)2{Cu(μ-X)(MeCN)}2] (2, X = Cl; 3, X = Br; 4, X = I; R = –OC10H6(μ-S)C10H6O–), whereas treatment with 0.5 equiv. of [Cu(MeCN)4]PF6 produces the mononuclear bischelated cationic complex, [{PhN(PR-κP)2}2Cu](PF6) (5). Single crystal X-ray structures of complexes 3 and 4 are reported. Complex 3 shows strong π–π stacking interactions between the naphthyl moieties, whereas complex 4 shows ligand-supported Cu⋯Cu metallophilic interactions.

Catalytic dehydroaromatization of n-alkanes by pincer-ligated iridium complexes - Ahuja, Ritu; Punji, Benudhar; Findlater, Michael; Supplee, Carolyn; Schinski, William; Brookhart, Maurice; Goldman, Alan S. (Nature Chemistry, 2011)
Aromatic hydrocarbons are among the most important building blocks in the chemical industry. Benzene, toluene and xylenes are obtained from the high temperature thermolysis of alkanes. Higher alkylaromatics are generally derived from arene–olefin coupling, which gives branched products—that is, secondary alkyl arenes—with olefins higher than ethylene. The dehydrogenation of acyclic alkanes to give alkylaromatics can be achieved using heterogeneous catalysts at high temperatures, but with low yields and low selectivity. We present here the first catalytic conversion of n-alkanes to alkylaromatics using homogeneous or molecular catalysts—specifically ‘pincer’-ligated iridium complexes—and olefinic hydrogen acceptors. For example, the reaction of n-octane affords up to 86% yield of aromatic product, primarily o-xylene and secondarily ethylbenzene. In the case of n-decane and n-dodecane, the resulting alkylarenes are exclusively unbranched (that is, n-alkyl-substituted), with selectivity for the corresponding o-(n-alkyl)toluene.

Cobalt-catalyzed C–H bond functionalizations with aryl and alkyl chlorides - Punji, Benudhar; Song, Weifeng; Shevchenko, Grigory A.; Ackermann, Lutz (Chemistry - A European Journal, 2013)
Inexpensive cobalt catalysts derived from N-heterocylic carbenes (NHC) allowed efficient catalytic C[BOND]H bond arylations on heteroaryl-substituted arenes with widely available aryl chlorides, which set the stage for the preparation of sterically hindered tri-ortho-substituted biaryls. Likewise, challenging direct alkylations with β-hydrogen-containing primary and even secondary alkyl chlorides proceeded on pyridyl- and pyrimidyl-substituted arenes and heteroarenes. The cobalt-catalyzed C[BOND]H bond functionalizations occurred efficiently at ambient reaction temperature with excellent levels of site-selectivities and ample scope. Mechanistic studies highlighted that electron-deficient aryl chlorides reacted preferentially, while the arenes kinetic C[BOND]H bond acidity was found to largely govern their reactivity.

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.

Chemodivergent dehydrogenative coupling of alcohols by 3d metal catalysts - Bansal, Sadhna; Punji, Benudhar (ChemCatChem, 2024)
Chemodivergent synthesis by transition metal catalysts is a straightforward and sustainable approach to achieving valuable organic compounds. Especially, the chemodivergent dehydrogenative couplings of alcohols with organic motifs to develop various saturated and unsaturated compounds are highly environmentally benign due to the reduced waste generation. In this concept review, we presented the 3d transition metal (Mn, Fe, Co, and Ni)-catalyzed chemodivergent synthesis of imines and amines, saturated and unsaturated carbonyl/alcohol compounds, saturated and unsaturated nitriles, N-heterocycles, and N-/C-alkylated indoles. The discussed reaction commanded two or three different products with high chemoselectivity by changing specific reaction parameters, but keeping the catalyst unchanged. Generally, the acceptorless dehydrogenative coupling (ADC) provides unsaturated moieties, whereas the borrowing-hydrogen (BH) process results in saturated compounds. Text for Table of Contents: An overview of the chemodivergent dehydrogenative coupling of alcohols by the Earth-abundant transition metal catalysts is discussed. image
Keywords: 3d metals; Alcohols; chemodivergent; dehydrogenative coupling; heterocycles

Copper-catalyzed regioselective C-H alkylation of phenol derivatives with unactivated alkyl chlorides: manifesting a Cu(I)/Cu(III) pathway - Verma, Suryadev K.; Punji, Benudhar (Journal of Catalysis, 2024)
The use of unactivated alkyl chlorides in regioselective C -H alkylation is a highly challenging process with diverse applications of alkylation strategy in drug discovery and agrochemistry. In this work, we report an efficient and cost-effective copper -catalyzed protocol for the coupling of unactivated alkyl chlorides with the C -H bond of phenol derivatives via 2-pyridinyl chelation assistance. The reaction shows a high level of regioselectivity, leading to an exclusive ortho alkylation and providing a broad scope with the endurance of numerous functionalities such as silyl, ether, thioether, pyrrolyl, indolyl, carbazolyl groups, including alkyl bearing fatty alcohol, nonylphenol, and vitamin E. Detailed mechanistic investigations suggest that the alkylation occurs through a two -electron oxidative addition of alkyl chloride to an active Cu(I) species. Deuterium labeling and kinetics experiments indicate a facile and reversible C -H bond activation process. Overall, the alkylation follows a Cu(I)/Cu(III) pathway involving chelation-assisted smooth C -H metalation and rate -limiting C-Cl oxidative addition of alkyl chloride.

CoBr2-catalyzed straightforward synthesis of quinoxalines via dehydrogenative coupling strategy - Dubey, Shivansh; Punji, Benudhar (Chemistry-an Asian Journal, 2025)
Establishing a benign and straightforward protocol for synthesizing biorelevant and synthetically valuable quinoxaline is very important. Herein, we report a simple and efficient protocol for the sustainable synthesis of diverse quinoxaline derivatives catalyzed by cobalt salt. The reaction proceeds through the dehydrogenative coupling of alkyl and aryl ethane 1,2-diols with aryl diamines in the presence of a catalytic CoBr2/K2CO3. The usage of the greener solvent 2-MeTHF and the release of H2 and H2O as the sole byproducts make the process advantageous. The protocol led to the synthesis of diverse quinoxalines bearing synthetically useful functionalities, such as fluoro, chloro, bromo, cyano, trifluoromethyl, and ether. The reaction is presumed to proceed via the dehydrogenative-condensation pathway involving a cobalt-hydride intermediate.
Keywords: cobalt; dehydrogenative coupling; heterocycles; ligand-free process; Quinoxaline